The Influence of Exploitative Leadership on Employees' Taking Charge Behavior: The Mediating Role of Organizational Identification and Moderating Role of Traditionality - Lazuardi Linus Saputra; Dodi Ria Atmaja; Joel Faruk Sofyan; Pawenary Pawenary (MES Bogor, 2025)
Jakarta's hospitality industry faces serious challenges in leadership practices that potentially undermine employees' proactive behavior amid post-pandemic operational pressures. This study aims to analyze the influence of exploitative leadership on taking charge behavior, the mediating role of organizational identification, and the moderating role of traditionality in that relationship. This quantitative research surveyed 150 employees from star-rated hotels in Jakarta through purposive sampling. Data were analyzed using Structural Equation Modeling-Partial Least Square (SEM-PLS). Results show that exploitative leadership has a significant negative effect on both taking charge behavior and organizational identification. Organizational identification strongly and positively influences taking charge behavior and partially mediates the relationship between exploitative leadership and taking charge behavior. Traditionality moderates the relationship by weakening the negative impact of exploitative leadership on organizational identification. The study recommends hotel management to prioritize building organizational identification through systematic employee engagement programs, strengthening accountable leadership systems, and developing a work environment that supports psychological safety and employee well-being. The research contributes by confirming the central role of organizational identification as a key psychological mechanism linking exploitative leadership with employees' proactive behavior in the Indonesian cultural context.